FLASHCARD-ASSISTED VOCABULARY LEARNING AMONG INDONESIA JUNIOR HIGH SCHOOL: A QUASI-EXPERIMENTAL PERSPECTIVE - Budiarti Putri Uleng; Musyrifah Mahfuddin; Nadya Nurhidayah Nurdin (Universitas Andi Djemma, 2026)
Vocabulary knowledge is essential in English as a Foreign Language (EFL) learning because it supports students’ communication skills and academic achievement. However, many Indonesian junior high school students still experience difficulties in vocabulary acquisition due to limited learning resources and instructional support. This study investigated the effectiveness of flashcard-assisted instruction in improving students’ vocabulary mastery at SMPN 2 Bua Ponrang. A quantitative pre-experimental design with a one-group pretest–posttest approach was employed. The participants were 22 eighth-grade students selected through cluster sampling. Data were collected using a vocabulary test administered before and after three flashcard-based instructional sessions. The results showed a significant improvement in students’ vocabulary mastery, with the mean score increasing from 65.90 in the pretest to 93.18 in the posttest. The findings indicate that flashcards effectively enhance vocabulary learning by promoting active engagement, visual learning, and vocabulary retention, making them a valuable instructional medium in EFL classrooms.